Blacks in and out of the left - Dawson, Michael C., 1951- (W.E.B. Du Bois lectures., 2013)
The radical black left has largely disappeared from the struggle for equality and justice. Michael Dawson examines the causes and consequences, and argues that the conventional left has failed to take race seriously as a force in reshaping American institutions and civil society. Black politics needs to find its way back to its radical roots.